Sinocrassula zhaotongensis (Crassulaceae), a New Species From China - Ling‐Nan Wei; Jing Zhao; Jian‐Rong Zhang; Zi‐Xian Liu; Jia‐Guan Wang (New Zealand Journal of Botany, 2026)
Sinocrassula zhaotongensis , a new species of Crassulaceae from Yunnan Province, China, is described and illustrated. Morphologically, S. zhaotongensis is characterized by a glabrous plant surface, asymmetrically triangular to lanceolate basal leaves, triangular‐lanceolate sepals, and triangular petals that are yellowish at the base with dense purple‐red stripes and spots on the surfaces upward. Phylogenetic analyses based on concatenated chloroplast and nuclear DNA sequences strongly support S. zhaotongensis as a distinct lineage and sister to S. adpressa .

Retraction notice to “Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study” [Sci. Total Environ. 883 (2023) 163662] - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Species synergy effects on milky aroma are conditioned by moisture-gradient driven pore evolution of protein–fat networks in fermented sausages - Futong Song; Ruren Li; Di Zhang; Jiaqi Zhao; Yafang Yao; Nan Zhang; Liangyan Rong (Meat Science, 2026)

Assessing the environmental regulation efficiency of Chinese cities for synergistic reductions in pollution and carbon emissions - Min Zhao; Rong Yuan; Xiaosong Ren; Nan Li (Environment, Development and Sustainability, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Direct CH4 electrosynthesis from CO2 via unmodified commercial carbon black: Structural synergy and defect-driven catalysis - Rong-Chun Zhong; Yu-Nan Liu; Zengrong Wang; Li-Yuan Zhao; Teng Shi; Qiang Sun (Fuel, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Transcriptome and Metabolome Combine to Analyze the Mechanism of Leaf Coloration Formation in Aeonium arboreum ‘Pink Sybil’ - Suhua Li; Rong Zhao; Haozhang Han; Lihua Zhang; Fang Wang; Nan Zhang; Rong Dong (Plant Molecular Biology Reporter, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Climate change enhances greening while human activities accelerate degradation in northern China's grasslands - Feifei Cao; Leizhen Liu; Yuping Rong; Nan Jiang; Lin Zhao; Qian Zhang; Zhitao Wu; Wenhui Zhao; Sheng Li (Science of The Total Environment, 2025)

Analysis of factors influencing microseismic detection and location in shale gas extraction areas of western Hubei - Wan-peng Hao; Li-fen Zhang; Yan-nan Zhao; Rong-ying Zheng; Wei-bing Qin; Jing-gang Li (Applied Geophysics, 2025)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Cloning and functional identification of anthocyanin synthesis-regulating transcription factor AaMYB4 in Aeonium arboreum Webb & Berthel ‘Halloween’ - Rong Zhao; Su-Hua Li; Hao-Zhang Han; Li-Hua Zhang; Fang Wang; Nan Zhang (Brazilian Journal of Botany, 2024)

Intestinal microbiota via NLRP3 inflammasome dependent neuronal pyroptosis mediates anxiety-like behaviour in mice exposed to 3.5 GHz radiofrequency radiation - Gui-qiang Zhou; Xing Wang; Peng Gao; Tong-zhou Qin; Ling Guo; Zhao-wen Zhang; Zhi-fei Huang; Jia-jin Lin; Yun-tao Jing; Hao-nan Wang; Chun-ping Wang; Gui-rong Ding (Science of The Total Environment, 2024)

Machine learning assisted combined systems of wastewater treatment plants with constructed wetlands optimal decision-making - Wei Dai; Ji-Wei Pang; Ying-Jun Zhao; Jie Ding; Han-Jun Sun; Hai Cui; Hai-Rong Mi; Yi-Lin Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Excessive fluoride induces ovarian function impairment by regulating levels of ferroptosis in fluorosis women and ovarian granulosa cells - Nan Geng; Siyuan Dong; Pengpeng Xie; Yi Zhang; Rong Shi; Chen Chen; Zhao Xu; Qun Chen (Reproductive Toxicology, 2024)

Characteristics of bacterial community structure in the sediment of Chishui River (China) and the response to environmental factors - Fei Di; Donghui Han; Guang Wang; Wenbo Zhao; Daokun Zhou; Nan Rong; Shou Yang (Journal of Contaminant Hydrology, 2024)

Developing a highly efficient, environmentally friendly and cost-effective copper sulfide semiconductor sponge for nuclear wastewater treatment under one sun - Wencai Bai; Mengjiao Liu; Kaifu Yu; Xin Cao; Jie Lian; Zhibin Zhao; Yong Xiang; Baoliang Xu; Tao Chen; Rong He; Nan Sun; Wenkun Zhu (Journal of Environmental Chemical Engineering, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Effect of enzyme-assisted fermentation on quality, safety, and microbial community of black soldier fly larvae (Hermetia illucens L.) as a novel protein source - Leying Meng; Liangxiao Ma; Jiahui Xu; Keming Rong; Nan Peng; Shumiao Zhao (Food Research International, 2023)

High-efficiency foam fractionation of anthocyanin from perilla leaves using surfactant-free active Al2O3 nanoparticle as collector and frother: Performance and mechanism - Lin Chen; Nan Hu; Chunquan Zhao; Xiaodan Sun; Rong Han; Yanyan Lv; Zhijun Zhang (Food Chemistry, 2023)

Efficient capture of iodine by charge-induced effect of nitrogen-rich ionic liquids - Shi-Jie Guo; Guo-Hao Zhang; Qiu-Hong Zhu; Chao Yu; Jia-Ying Liu; Xiao-Lan Yang; Song Qin; Nan-Rong Zhao; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Ferrous ion enhanced Fenton-like degradation of emerging contaminants by sulfidated nanosized zero-valent iron with pH insensitivity - Jia-Qi Chen; Guan-Nan Zhou; Rong-Rong Ding; Qi Li; Han-Qing Zhao; Yang Mu (Journal of Hazardous Materials, 2023)

Experimental Investigation on Particle Breakage Behavior of Marine Silica Sand under High-Stress Triaxial Shear - Rong Chen; Tong Zhao; Zhiyong Wu; Dongxue Hao; Nan Xue; Chi Yuan (Journal of Marine Science and Engineering, 2023)
There is often obvious particle breakage for silica sand under high-stress, which will lead to the bearing capacity reduction and excessive settlement of the foundation. This paper focuses on the particle breakage characteristics of marine silica sand from the East China Sea under high-stress conditions. A series of conventional triaxial tests for silica sand, including consolidated drained (CD) and consolidated undrained (CU) shear tests, were conducted under the confining pressures in the range of 2–8 MPa to investigate the breakage rule during the shearing process. The developments of particle breakage index Br with axial strain ε1 and volumetric strain εv present hyperbolic and linear trends, respectively. A hyperbolic model was adopted to describe the relationship of Br and ε1 and the corresponding model parameters were obtained. The particle breakage index also has a good correlation with the input work per unit volume under various average stresses, regardless of the stress history. Furthermore, the relationship between the fractal dimension and the particle breakage was studied based on the particle size distribution curve. It is concluded that the fractal dimension increases in an up–convex hyperbolic trend with the increase of particle breakage index. The dividing radius for whether the silica sand particles exhibit the fractal features is determined as approximately 0.4 mm. This is anticipated to provide reference and supplementary test data for analyzing sand constitutive models/environments regarding particle crushing.

Influence mechanism of financial development on carbon emissions from multiple perspectives - Xiaosong Ren; Min Zhao; Rong Yuan; Nan Li (Sustainable Production and Consumption, 2023)

RETRACTED: Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Multiple metal(loid)s bioaccessibility from cooked seafood and health risk assessment - Wen Liao; Wenbo Zhao; Ye Wu; Nan Rong; Xiaowei Liu; Kaiming Li; Guang Wang (Environmental Geochemistry and Health, 2020)

Neo-debromoaplysiatoxin C, with new structural rearrangement, derived from debromoaplysiatoxin - Yang-Hua Tang; Ting-Ting Liang; Ting-Ting Fan; Lawrence Jordan Keen; Xiao-Dan Zhang; Lin Xu; Qi Zhao; Rong Zeng; Bing-Nan Han (Natural Product Research, 2020)

Expression of the subgroup IIIf bHLH transcription factor CpbHLH1 from Chimonanthus praecox (L.) in transgenic model plants inhibits anthocyanin accumulation - Rong Zhao; Xiaoxi Song; Nan Yang; Longqing Chen; Lin Xiang; Xiu-Qun Liu; Kaige Zhao (Plant Cell Reports, 2020)

Functional characterization of a low-frequency V1937I variant in FASN associated with susceptibility to esophageal squamous cell carcinoma - Xiaoyang Wang; Jianbo Tian; Qianyu Zhao; Nan Yang; Pingting Ying; Xiating Peng; Danyi Zou; Ying Zhu; Rong Zhong; Ying Gao; Jiang Chang; Xiaoping Miao (Archives of Toxicology, 2020)

p70S6K activation promotes the transdifferentiation of fibroblasts to myofibroblasts in pterygium tissue growth on the cornea - Xin-Rong Zhao; Ming-Chang Zhang; Hua-Tao Xie; Nan Ji; Le-Tian Sun (Biotechnology Letters, 2018)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Attenuation of Reserpine-Induced Pain/Depression Dyad by Gentiopicroside Through Downregulation of GluN2B Receptors in the Amygdala of Mice - Shui-bing Liu; Rong Zhao; Xu-sheng Li; Hong-ju Guo; Zhen Tian; Nan Zhang; Guo-dong Gao; Ming-gao Zhao (NeuroMolecular Medicine, 2014)

GWAS-linked GAK locus in Parkinson’s disease in Han Chinese and meta-analysis - Nan-Nan Li; Xue-Li Chang; Xue-Ye Mao; Jin-Hong Zhang; Dong-Mei Zhao; Eng-King Tan; Rong Peng (Human Genetics, 2012)

Expansins are involved in cell growth mediated by abscisic acid and indole-3-acetic acid under drought stress in wheat - Mei-rong Zhao; Yang-yang Han; Ya-nan Feng; Feng Li; Wei Wang (Plant Cell Reports, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)